The More, the Better? The Impact of Instructional Time on Student Performance - Alejandra Cattaneo; Chantal Oggenfuss; Stefan C. Wolter (Center for Economic Studies and ifo Institute (CESifo), 2016)
Although instruction time is an important and costly resource in education production, there is a remarkable scarcity of research examining the effectiveness of its use. We build on the work of Lavy (2015) using the variance of subject-specific instruction time within Switzerland to determine the causal impact of instruction time on student test scores, as measured by the international PISA test (2009). We extend the analyses in two ways and find that students must differ considerably in the time needed to learn. This difference is supported by our findings that the effectiveness of instructional time varies substantially between different school (ability) tracks and that additional instruction time significantly increases the within-school variance of subject-specific test scores.
Keywords: C21; I21; I25; 330; instruction time; PISA; fixed-effect models; tracking